Autonomous Behavior Intelligence Control of Self-Evolution Mobile Robot for High-Voltage Transmission Line in Complex Smart Grid. (5th November 2020) - Jiang, Wei; Zuo, Gan; Zou, De Hua; Li, Hongjun; Yan, Jiu Jiang; Ye, Gao Cheng
Abstract : In complex smart grid, the power maintenance robot is important equipment to ensure the reliable operation of high-voltage lines and it is a useful exploration to realize high-quality power transmission. In view of the increasingly prominent contradiction between the robot single operation function and the diversification of power grid maintenance operations, additional with the robot weak autonomous operation and intelligent behavior ability, this paper proposes a new configuration of a reconfigurable power robot with terminal functions and its autonomous operation behavior control method for the three typical tasks which are the high-voltage transmission line insulators, drainage plates, and dampers maintenance. Through the analysis and planning of the robot operation behavior, the robot finite state machine (FSM) model in the three operation states has been established. Through the introduction of the state transfer function in the FSM, the automatic switching control between the robot key operation states can be realized, and the robot motion planning can be optimized. The movement and working flow of the robot improve the robot operation intelligence and operation efficiency. Based on this, the robot autonomous operation control system has been designed and the robot physical prototype has been developed for three maintenance tasks of insulators, drainage plates, and dampers. Finally, simulation experiments and field operation tests verify the effectiveness and engineering practicability of the proposed method. Compared with traditional manual control, the autonomous behavior control method can significantly improve the robot operational efficiency and operational intelligence. At the same time, the robot multitask function and autonomous behavior control under different tasks can be realized and the method has strong versatility for different task objects and different line environments. The research and its promotion have important theoretical significance and practical application value for the power system operation and maintenance integration management.